(untitled) (Annals of Medical Research, 2021)
Aim: The frequency of placenta previa (PP) is increasingly rising due to the increase in caesarean ratio. The aim of this study is to investigate the role of the white blood cell (WBC) in the preoperatively taken complete blood specimen in foreseeing whether hysterectomy will be performed or not in patients with placenta previa totalis.Materials and Methods:Two hundred fifty-seven (257) patients who experienced caesarean due to placenta previa totalis (PPT) in Ondokuz Mayis University between 2010 and 2018 had been surveyed retrospectively. The results of the preoperative Complete Blood Count (CBC) of the Placenta PreviaTotalis (PPT) patients in which either hysterectomy was applied or not, demographic characteristics, other follow-up and treatment results were accessed via system records and file surveys. The primary outcome is the role of preoperative White Blood Cell (WBC) levels in predicting hysterectomy, Results: WBC median values in the pre-operative complete blood specimen of the patients with placenta previa totalis demonstrate difference between the patients with hysterectomy and those without hysterectomy. While the median value was as 9.7 109/L in the patients who could be recovered with treatments apart from hysterectomy, this was obtained as 11.3109/L in the patients in which hysterectomy was applied (p=0.007).Conclusion: Increase in WBC in the pre-operative blood specimen of the patients with diagnosis of Placenta Previa Totalis may be guiding whether hysterectomy will be applied or not.Keywords: Placenta previa; hysterectomy; leukocytosis; caesarean.